Predictors of Perinatal Outcome in Full term Neonates with Hypoxic Ischemic Encephalopathy. - Aljanabi, Muhi K.; Shehab, Mohamoud; Rasheed, Rihab S. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Hypoxic ischemic encephalopathy (HIE) means failure to establish effective spontaneous breathing after complete delivery & leads to many changes if not diagnosed or treated immediately as mental retardation, cerebral palsy and epilepsy.Objective: to study the demographic and clinical predictors of perinatal outcome in full term neonates with hypoxic ischemic encephalopathy.Methods: Forty two neonates were diagnosed as cases of hypoxic ischemic encephalopathy by specialist pediatricians & admitted in Children Welfare Teaching Hospital & Al Kut Hospital in the period from January 2008 to March 2009. Predictors studied were sex, birth weight, Apgar scores at 1,5,15 min., meconium aspiration, lethargy, muscle tone , convulsion. Outcome was also recorded. Statistical analysis was done by the use of fisher exact test. Results: The total number studied were forty two neonate. Half of them were born at home & others in hospital with a male / female ratio= 1/1. Thirty three newborns had normal birth weight & nine had low birth weight. the mean apgar score recorded for sixteen neonate born in hospital at 1 minute = 4.3 ± 1.922, at 5minute=6.06± 2.08 and at 15 minute = 6.62± 2.33. out of the 21 hospital born babies with HIE, 6 died and 15 improved and out of 21 home born babies with HIE 4 died and 17 improved. The difference was not statistically significant. P. value.0.7.Conclusion: Full term newborn babies with HIE died more frequently if they were males, with low birth weight, with Apgar scores of`< 4 at 1 min., 4-7 at 5 and 15 min., meconium aspiration, convulsion, hypotonic. Hypertonia and lethargy were noticed to be associated significantly with perinatal mortality in newborns with HIE.